Influence of cutout shapes on postbuckling of functionally graded material plate under inplane-compressive load - Jamali, Hamed (2014)
Functionally graded materials (FGM) are composite materials with microstructure gradation optimized for the functioning of engineering components. For the case of fibrous composites, the fiber density is varied spatially, leading to variable material properties tailored to specific optimization requirements. There is an increasing demand for the use of such intelligent materials in space and aircraft industries. The current preferred methods to study engineering components made of FGM are mainly modeling particularly those that are finite element (FE) based on rectangular and circular plate/shell with constant thickness and study on the structures with nonlinearity on shape have not yet sufficiently matured. Hence this thesis reports the research study on postbuckling and stability analyzing of FGM plate/shell with four different cut-out shapes including circular, square, horizontal elliptical and verticalelliptical cutout shape under different boundary conditions. Comparison for FE model performed in two stages, including FGM plate and Postbuckling of FGM plate, to verify the model and Postbuckling of model. The verified model was used in current research study for analyzing the FGM plate with different cutout shapes. Validation of the results of this study has been done by verifying the results with Postbuckling results of aluminum plate. The pustbuckling analysis of FGM Plate subjected to edge loading (edge shortening and edge compression) was performed through finite element software ABAQUS. The structures considered in this study are functionally graded in a single direction and elastic region was assumed for materials which were used within all analysis stages in this research. This study has shown that tightening the boundary of plate increases the stability of the plate and the plate with elliptical shape cutout has the highest Postbuckling load which means the plate with vertical elliptical cutout shape has the higher stability among the others. The elliptical cutout shape is the best shape for having higher mechanical stability and Postbuckling resilience.